The altering cellular components and function in tumor microenvironment during remissive and relapsed stages of anti-CD19 CAR T-cell treated lymphoma mice - Zhao, Kai; Ren, Chunxiao; Tang, Donghai; Zhao, Li; Chen, Xianxian; Wang, Ying; Xu, Kailin (Frontiers in Immunology, 2023)
Anti-CD19 chimeric antigen receptor (CAR) T cells represent a highly promising strategy for B cell malignancies. Despite the inspiring initial achievement, the remission in a notable fraction of subjects are short-lived and relapse remains a major challenge. Tumor microenvironment (TME) was proved to be aroused by CAR T cells, however, little is known about the dynamic characteristics of cellular components in TME especially during the different phases of disease after anti-CD19 CAR T cell treatment. We took advantage of an immunocompetent model receiving syngeneic A20 lymphoma cells to dissect the changes of TME with or without CAR T cell injection. We found that anti-CD19 CAR T cell treatment attenuated the symptom of lymphoma and significantly prolonged mice survival through eradicating systemic CD19+ cells. Increased myeloid subsets, including CD11c+ DCs and F4/80+ macrophages with higher MHC Ⅱ and CD80 expression in bone marrow, spleen, and liver were detected when the mice reached remission after anti-CD19 CAR T treatment. Compared to mice without anti-CD19 CAR T administration, intrinsic T cells which were triggered to produce more IFN-γ and TNF-α. However, some lymphoma mice relapsed by day 42 after therapy, which coincided with CAR T cell recession, decreased myeloid cells activation and increased Treg cells. Elevated intrinsic T cells with high PD-1 and TIGIT exhausted signatures and attenuated cytotoxicity in TME were associated with the late stage relapse of CAR T cell treatment. In summary, the cellular composition of TME as allies of CAR T cell possibly contribute to the anti-tumor efficacy at the initial stage, whereas anti-CD19 CAR T cell disappearance and host response immunosuppression may work together to lymphoma relapse after an initial near-complete elimination phase.